Total pectoral ectopia cordis and other congenital malformations in a calf. - Eröksüz, H.; Metin, N.; Eröksüz, Y. (My University, 1998)
[Abstract Not Available]
Keywords: Animals; Cattle; Female; Heart Defects, Congenital; Heart Failure, Congestive; Liver Cirrhosis; Pericardium; MLCS; MLOWN; animal; animal disease; article; case report; cattle; congenital heart malformation; congenital malformation; congestive heart failure; female; liver cirrhosis; pericardium